DNA methylation and transcription onset in the brain. (June 2017) - Massart, Renaud; Suderman, Matthew; Mongrain, Valerie; Szyf, Moshe
Aim: The goal of this study was to test the state of methylation of transcription start positions in DNA that are actively involved in transcription.Materials & methods: We used sequential ChIP-bisulfite-sequencing with an antibody to RNpolII-PS5 to map the state of methylation of actively transcribing transcription start sites (TSS).Results: TSS that RNApolII-PS5 physically bind to, are ubiquitously unmethylated. TSS that appear to be both heavily methylated and transcriptionally active are truly a mixture of unmethylated TSS with bound RNApolII-PS5 in some nuclei and unbound methylated TSS in other nuclei.Conclusion: TSS DNA methylation is universally inconsistent with transcription onset and could therefore serve as a digital count of the fraction of nuclei with methylation-silenced TSS.